ChemInform Abstract: P2Et Phosphazene: A Mild, Functional Group Tolerant Base for Soluble, Room Temperature Pd‐Catalyzed C—N, C—O, and C—C Cross‐Coupling Reactions. Issue 45 (November 2015) - Buitrago Santanilla, Alexander; Christensen, Melodie; Campeau, Louis‐Charles; Davies, Ian W.; Dreher, Spencer D.
Abstract The organic superbase P2‐Et is shown to possess distinct reactivity across a diverse set of cross‐coupling reactions at room temperature.